Comportamento espermatogonial em ratos após irradiação e submetidos à supressão hormonal - Amanda Vasconcelos de Albuquerque (2013)
Ionizing radiation has been shown to arrest spermatogenesis despite the presence of surviving stem spermatogonia, by blocking their differentiation. This block is a result of damage to the somatic environment and is reversed when gonadotropins and testosterone are suppressed, but the mechanisms are still unknown. We examined spermatogonial differentiation and Sertoli cell factors that regulate spermatogonia after irradiation, during hormone suppression, and after hormone suppression combined with Leydig cell elimination with EDS. The results showed that the numbers and cytoplasmic structure of Sertoli cells are unaffected by irradiation; that only a few Aund spermatogonia and even fewer A1 spermatogonia remained and that immunohistochemical analysis showed that Sertoli cells still produced KITG and GNDF. Some of these cells expressed KIT-receptor, demonstrating that the failure of differentiation was not a result of the absence of the KIT system. Hormone suppression resulted in an increase in Aund spermatogonia within 3 days, a gradual increase in KIT-positive spermatogonia, and differentiation mainly to A3 spermatogonia after 2-weeks. KITLG protein expression did not change after hormone suppression indicating that it is not a factor in the stimulation. However, GDNF increased steadily after hormone suppression, which was unexpected since GDNF is supposed to promote stem spermatogonial self-renewal and not differentiation We conclude that the primary cause of block in spermatogonial development is not due to Sertoli cell factors such (KITLG\GDNF) or the KIT receptor. Since elimination of Leydig cells in addition to hormone suppression resulted in differentiation to the A3 stage within 1 week, Leydig cell factors were not necessary for spermatogonial differentiation.